TENSES IN ENGLISH FRIDAY SERMON OF UNIVERSITY OF DARUSSALAM GONTOR - Diana Sopha; Ayu Melati Ningsih (PHILOLOGY Journal of English Language and Literature, 2023)
This research is concentrated in the aspect of structure especially tenses. The existence of tenses in English is an obligatory in opposite there is no English without the use of tenses. Thus tense has a very significant function in English. With qualitative research, it can be found that several types of tenses are used in delivering sentences of English Friday Sermon. They are the most dominant tense is Simple Present Tense. Then the other tenses used in English Friday Sermon are Present Perfect Tense, Simple Future Tense and Simple Past Tense.